The Mars Analysis Correction Data Assimilation (MACDA) Dataset V1.0. (6th June 2014) - Montabone, L.; Marsh, K.; Lewis, S. R.; Read, P. L.; Smith, M. D.; Holmes, J.; Spiga, A.; Lowe, D.; Pamment, A.
<x xml:space="preserve">Abstract</x> The Mars Analysis Correction Data Assimilation (MACDA) dataset version 1.0 contains the reanalysis of fundamental atmospheric and surface variables for the planet Mars covering a period of about three Martian years (a Martian year is about 1.88 terrestrial years). This has been produced by data assimilation of observations from NASA's Mars Global Surveyor (MGS) spacecraft during its science mapping phase (February 1999–August 2004). In particular, we have used retrieved thermal profiles and total dust optical depths from the Thermal Emission Spectrometer (TES) on board MGS. Data have been assimilated into a Mars global climate model (MGCM) using the Analysis Correction scheme developed at the UK Meteorological Office. The MGCM used is the UK spectral version of the Laboratoire de Météorologie Dynamique (LMD, Paris, France) MGCM. MACDA is a joint project of the University of Oxford and The Open University in the UK.